Association of Self-Paced Physical and Cognitive Activities Across the First Week Postconcussion With Symptom Resolution in Youth. Issue 2 (March 2021) - Yang, Jingzhen; Yeates, Keith Owen; Shi, Junxin; Sullivan, Lindsay; Xun, Pengcheng; Taylor, H. Gerry; Tiso, Michael; Pommering, Thomas; MacDonald, James; Cohen, Daniel M.; Hautmann, Amanda; Asa, Nicole; et al.
Abstract : Objective: To examine the association of objectively measured, self-paced physical and cognitive activities across the first week postconcussion with symptom resolution in youth. Setting: Emergency department or concussion clinics. Participants: Youth aged 11 to 17 years with physician-confirmed concussion. Design: Prospective cohort with repeated measures. Main Measure(s): Days from injury to symptom resolution, based on daily ratings by youth on the Post-Concussive Symptom Scale. Physical and cognitive activities were assessed using an ActiGraph and a Narrative Clip, respectively. Results: A total of 83 youth participants were included ( n = 54 [65%] males; mean age = 14.2 years, SD = 1.9). While self-paced daily physical and cognitive activities increased across the first week postinjury, daily postconcussion symptoms decreased. Increased daily step count was associated with an increased likelihood of early symptom resolution (hazard ratio [HR] = 1.17; 95% confidence interval [CI], 1.02-1.34). However, this association was not statistically significant after adjusting for acute postconcussion symptoms and other covariates. Greater school attendance time was associated with earlier symptom resolution (adjusted HR = 1.14; 95% CI, 1.02-1.27). Conclusion: Self-paced physical and cognitive activities across the first week postinjury alone neither hastened nor prolonged concussion recovery. Youth with concussion may have some latitude to determine their activity levels.